2021
DOI: 10.1080/0312407x.2021.1904427
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Workers’ Challenges in Hearing Children’s Voices in Family Support Services

Abstract: Research into children's voices continues to receive significant attention due to the limited progress made around the world in meeting Article 12 of the Convention on the Rights of the Child: the right to be heard and participate in decision making. However, there is a paucity of research providing insights into children's voices in family support services linked with the child protection system. This paper contributes new understandings into the everyday practice experiences of 46 frontline urban and regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…This is apparently embedded in a more general preference of protection over participation and an aversion to risk: Workers strive to keep children safe and assume that the inclusion of children's own views in the decision-making process poses a risk because children are unable to make safe choices (Healy, 1998;McCarthy, 2016;Seim & Slettebø, 2017;van Bijleveld et al, 2015;van Bijleveld et al, 2020;Vis, Holtan, & Thomas, 2012). In addition, it is suggested that workers sometimes lack knowledge about children's rights (Stafford, Harkin, Rolfe, Morley & Burton, 2022;van Bijleveld et al, 2020) and that they may not have the necessary skills in communicating with children to facilitate their participation (Handley & Doyle, 2014;Križ & Skivenes, 2017;Križ & Roundtree-Swain, 2017;O'Reilly & Dolan, 2016;Pölkki, Vornanen, Pursiainen & Riikonen, 2012;Seim & Slettebø, 2017;van Bijleveld, Dedding & Bunders-Aelen, 2014). Moreover, there appears to be a lack of knowledge about child development (Handley & Doyle, 2014).…”
Section: Factors Determining the Likelihood Of Child Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is apparently embedded in a more general preference of protection over participation and an aversion to risk: Workers strive to keep children safe and assume that the inclusion of children's own views in the decision-making process poses a risk because children are unable to make safe choices (Healy, 1998;McCarthy, 2016;Seim & Slettebø, 2017;van Bijleveld et al, 2015;van Bijleveld et al, 2020;Vis, Holtan, & Thomas, 2012). In addition, it is suggested that workers sometimes lack knowledge about children's rights (Stafford, Harkin, Rolfe, Morley & Burton, 2022;van Bijleveld et al, 2020) and that they may not have the necessary skills in communicating with children to facilitate their participation (Handley & Doyle, 2014;Križ & Skivenes, 2017;Križ & Roundtree-Swain, 2017;O'Reilly & Dolan, 2016;Pölkki, Vornanen, Pursiainen & Riikonen, 2012;Seim & Slettebø, 2017;van Bijleveld, Dedding & Bunders-Aelen, 2014). Moreover, there appears to be a lack of knowledge about child development (Handley & Doyle, 2014).…”
Section: Factors Determining the Likelihood Of Child Participationmentioning
confidence: 99%
“…Thus, a parent-related variable (reluctance towards child participation) is intertwined with the worker-parent relationship. In addition, the worker-child relationship seems to matter: child participation may be more likely if the level of familiarity and trust between the worker and the child is higher (M. Bell, 2002;Cossar et al, 2016;Seim & Slettebø, 2017;Stafford et al, 2022;Strandbu, 2004;Vis et al, 2012). At the case level, there is some evidence that a more serious degree of risk (as evidenced, for example, in substantiated child abuse and neglect or domestic violence) makes it less likely for case workers to encourage child participation (Archard & Skivenes, 2009;Healy & Darlington, 2009;Seim & Slettebø, 2017;Vis & Thomas, 2009).…”
Section: Factors Determining the Likelihood Of Child Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of five WorldCafé workshops were held across two metropolitan and three regional locations. Practitioner experiences revealed four broad, intersecting barriers to child-inclusive practice, including conceptual, organisational, programmatic, and direct practice skills and resources [8]. While some pockets of child-inclusive practice were evident, indicating significant potential for expansion, there was an overall lack of intentional engagement with children as a consistent feature of practice across program sites.…”
Section: The Empowering Children's Voices Research Projectmentioning
confidence: 99%
“…According to Sinclair [6] (p. 329), this shift in thinking to value children's voices and participation has emerged from the coalescence of several developments: the demands for service user participation from the consumer movement; the promotion of a global children's rights agenda; and critical approaches to social science that contests the conception of children as 'incomplete adults'. However, despite these developments and a commitment on the part of practitioners to recognise children as competent social actors, it is widely acknowledged that meaningful child-inclusive practice has struggled to move beyond rhetorical practice (see for example [2,4,[6][7][8][9][10][11]). Holt [11] argues that this is because of the tension between the rights versus welfare debate-where children's participation is considered to over-burden them with adult-like responsibility, which risks their corresponding right to protection and threatens their experience of childhood.…”
Section: Introductionmentioning
confidence: 99%